2011
DOI: 10.1093/rpd/ncr373
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose to neonates undergoing X-ray imaging in special care baby units in Iran

Abstract: Radiographic imaging has a significant role in the timely diagnosis of the diseases of neonates in intensive care units. The estimation of the dose received by the infants undergoing radiographic examination is of great importance, due to greater more radiosensitivity and longer life expectancy of the neonates and premature babies. In this study, the values of entrance skin dose (ESD), dose area products (DAPs), energy imparted (EI), whole-body dose, effective dose and risk of childhood cancer were estimated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…5,11 Over the last two decades, a few radiation dosimetric studies have been published regarding exposure to ionising radiation from radiographs by preterm infants in a neonatal unit. [12][13][14][15][16][17][18][19][20][21] The mean gestational age (GA) of subjects ranged from 25.4 to 33.0 weeks. 17,21 The amount of radiation absorbed depends mainly on the number of radiographs received and the radiation dose of each radiograph.…”
Section: Introductionmentioning
confidence: 99%
“…5,11 Over the last two decades, a few radiation dosimetric studies have been published regarding exposure to ionising radiation from radiographs by preterm infants in a neonatal unit. [12][13][14][15][16][17][18][19][20][21] The mean gestational age (GA) of subjects ranged from 25.4 to 33.0 weeks. 17,21 The amount of radiation absorbed depends mainly on the number of radiographs received and the radiation dose of each radiograph.…”
Section: Introductionmentioning
confidence: 99%
“…In a comprehensive research project carried out by Asadinezhad M, Bahreyni Toossi MT in 2008 ,they proposed the first Iranian diagnostic reference levels(9), (10).ESD is amount of skin absorbed dose at the entrance point of the X-ray beam.ESD measurement can be performed directly or indirectly. Termo Luminecent Dosimeter (TLD)measures the ESD directly (11).…”
Section: Introductionmentioning
confidence: 99%
“…Bahreyni Toossi et al [5] reported ESD value of 76.3 µGy and DRL value of 88 µGy for neonatal chest X-rays in Mashhad. Similarly, Faghihi et al [14] reported ESD value of 56.6 µGy for neonatal chest X-rays in Shiraz.…”
Section: Although Discovery Of X-rays By Wilhelm Conradmentioning
confidence: 88%